FAKTOR-FAKTOR PENYEBAB KELELAHAN KERJA PADA PEKERJA BANK X KANTOR CABANG MAGELANG - Fahmi, Tiko Aprilano; Jayanti, Siswi; Suroto, Suroto (Jurnal Kesehatan Masyarakat (Undip), 2015)
Bank was a service company which the company’s quality was determined by the role of human resources that they had. Banking employees was more likely had under pressure in his life that could lead to fatigue. The impact of fatigue would lead to decline in performance, efficiency, productivity, and increase the level of work-related errors. The aim of this study was to analyze the factors associated with fatigue on bank workers X branch Magelang. This was a explanatory research with cross sectional approach. The study was conducted by using questionnaires and observations of the bank worker X branch Magelang. In this study the total population was taken as many as 28 workers.Chi Square test was used to analyze the data. The result of the research were39.3% of workers suffered mild fatigue and 60.7% moderate fatigue. From the statistical test can be obtained that there wereassociation between gender (p value=0,003), association between sleeping hours (p value=0,002), association between smoking habit (p value=0,023), association between mental workload (p value=0,025) with fatigue.There were no association between working period (p value=0,355) andno association health condition (p value=1,000)with fatigue. Workers need adequate rest such as sleep 8 hours before doing their duty.